Growth and survival rate of freshwater lobster (Cherax quadricarinatus) fed different forage feed. Issue 1 (January 2022) - Samad, A P A; Isma, M F; Ayuzar, E; Ilhamdi,; Humairani, R; Santi, F
Abstract: Lobster is among freshwater crustaceans which is potentially cultivated in aquaculture system. This present study was conducted to determine the growth and survival rate of freshwater lobster Cherax quadricarinatus fed different forage feed. The experimental methode used a completely randomized design consisted of 4 treatments in triplicate: commercial diet (PL), commercial diet and carrots (PW), commercial diet and potatoes (PK) and commercial diet and sweet potatoes (PU). The experimental lobsters were 5-7 cm in size and 6-8 g in weight. Results indicated that forage feeding can affect the total weight and length, weight gain, specific growth rate and survival rate of lobster. Data showed the best weight gain and specific growth rate were found in PW (34.37±0.30%) and (1.05±0.03%), respectively. The lowest survival rate was seen in PU at 86.67%. However, the best feed conversion ratio gained by PL at 1.74±0.09. This study suggested that the combination of commercial diet with carrots provided the best growth performances in freshwater lobster Cherax quadricarinatus .